PEMIMPIN JENIUS UNTUK MENUJU SEKOLAH ATAU MADRASAH UNGGULAN DI MIS ZAKARIA KOTA BANDUNG - Nailan, Akhmaliah Siti; Sulastri, Asri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The relationship between genius leaders in realizing superior schools or madrasas encouraged the author to conduct research at MIS Zakaria Bandung City. In essence, humans on this earth are leaders. The Principal of the School/Madrasah and the teacher are a leader for the students. Being a leader is not enough if you only rely on intelligence from the academic side, but you must have social and emotional sensitivity, and have the ability to regulate, direct, and influence someone's actions. This research aims to find out the characteristics of genius leaders and their relationship with superior schools or madrasas. This research method is included in the quantitative descriptive research method. The data collection techniques used are in the form of questionnaires and interviews. The results of the study show that there is a link between genius leaders and superior schools or madrasas. This is evidenced by the score obtained is 75 or the percentage is 81%. The qualification percentage score of 81% is in the good category. So it can be concluded that the leadership at MIS Zakaria, precisely in genius leaders, is included in the good category.